The effect of severe maternal obesity on the accuracy of ultrasonographic fetal weight estimation: a prospective cohort study. (18th April 2012) - Denison, FC; Thomson, A; Walker, J; Forbes, SF; Norman, JE; Stock, SJ; Reynolds, RM
Abstract : Objectives: To assess the accuracy of fetal biometry measurements in predicting birthweight and to compare serial fetal biometry measurements in women with very severe obesity and lean controls. Methods: 174 very severely obese (body mass index, BMI>40kg/m2) and 55 lean (BMI<25kg/m2) women with a singleton pregnancy were recruited to a prospective longitudinal study assessing the effect of maternal obesity on pregnancy outcome. Ultrasonographic fetal biometry was measured at booking, 20, 28 and 36 weeks gestation, and gestation, gender and birthweight recorded at delivery. Estimated fetal weight (EFW) at 36 weeks was calculated using Hadlock formulae. Estimated birthweight (EBW) was calculated by adjusting EFW at 36 weeks for scan-to-delivery interval. Results: Observed and expected birthweight were strongly correlated using Hadlock formulae incorporating the AC, and AC and HC in both the very severely obese (r=0.68 and r=0.65, both p<0.0001) and lean cohorts (r=0.63 and r=0.67, both p<0.001). 95% limits of agreement between estimated and actual birthweights were similar with both formulae and did not differ between lean and obese. Head circumference (HC) measurements was significantly greater in obese compared to lean women at 20 weeks gestation (p<0.05), and abdominal circumference (AC) significantly greater in obese compared to lean at 28 and 36 weeks gestation (both p<0.01). Conclusion: Estimated birthweight derived from fetal biometry measurements during the late third trimester of pregnancy are as accurate in very severely obese compared to lean women. This information may inform obstetric management and delivery planning in very severely obese women, which may minimise risk and improve perinatal outcome.